Toward SDGs: Forest, Market and Human Wellbeing Nexus in Indian Western Himalayas - Dobriyal, Pariva; Badola, Srishti; Hussain, Syed Ainul; Badola, Ruchi (Frontiers in Ecology and Evolution, 2022)
The wellbeing of mountain communities is determined by the availability and accessibility of ecosystem goods and services. We assessed the relationship between forest quality and wellbeing of local communities of Nanda Devi Biosphere Reserve (NBBR), Western Himalayas, India. To assess the status of wellbeing of local people 14 relevant Sustainable Development Goals of the United Nations were used as indicators. Data on these indicators was collected in 22 villages that were selected based on secondary demographic information, distance from and the state of the forest resources i.e., degraded and less-degraded. Semi-structured questionnaire-based interviews were conducted in randomly selected households (n=764). The households located close to forests scored higher on wellbeing indicators than did the households located further away from forests as they have better accessibility to forest resources and freshwater which provides alternative for market and agricultural products. Households with access to less-degraded resources also had access to wild fruits, vegetables and medicinal plants adding to their food and health security. Our study found that the combination of climate change, declining forest resources and the expansion of the market-based economy is leading to shifts in traditional cropping patterns and hence on the nutritional status and forest use patterns of local people, making them vulnerable to diseases and hunger. Accessibility to an intact forest patch near a village contributes to the wellbeing of people and increases their resilience in face of climate change and changes dictated by the market forces.